2012
DOI: 10.1161/hypertensionaha.111.181644
|View full text |Cite
|
Sign up to set email alerts
|

Role of Uncoupled Endothelial Nitric Oxide Synthase in Abdominal Aortic Aneurysm Formation

Abstract: It has been shown that eNOS uncoupling occurs in hypertension and atherosclerosis. However its causal role in vascular pathogenesis has not been previously characterized. Here, we challenged eNOS pre-uncoupled hph-1 mice (deficient in eNOS cofactor tetrahydrobiopterin biosynthetic enzyme GTPCHI) with Ang II (0.7 mg/kg/day, 14 days). Both wild-type (WT) and hph-1 groups developed hypertension similarly up to day 6 to 7. Thereafter approximately 14% of Ang II-infused (0.7 mg/kg/day) hph-1 mice (n=72) started to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

26
194
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 106 publications
(222 citation statements)
references
References 48 publications
26
194
1
1
Order By: Relevance
“…Next, a mouse aortic disc angiogenesis assay was carried out. In vivo siRNA transfection was achieved by lipid-based transfection kit as previously described (12)(13)(14). siRNA targeting mouse PTP1B was found highly effective in attenuating PTP1B expression in mouse aortas (Fig.…”
Section: Effects Of Ptp1b Overexpression On Vegf-induced Phosphorylatmentioning
confidence: 99%
“…Next, a mouse aortic disc angiogenesis assay was carried out. In vivo siRNA transfection was achieved by lipid-based transfection kit as previously described (12)(13)(14). siRNA targeting mouse PTP1B was found highly effective in attenuating PTP1B expression in mouse aortas (Fig.…”
Section: Effects Of Ptp1b Overexpression On Vegf-induced Phosphorylatmentioning
confidence: 99%
“…Recent studies from our laboratory have identified that uncoupling of endothelial nitric oxide synthase (eNOS), in which the normally nitric oxide (NO)-producing eNOS produces superoxide to induce oxidative stress, plays a causal role in the formation of AAA (10,29). This uncoupling of eNOS is caused by a reduced bioavailability of tetrahydrobiopterin (H 4 B), which is the essential cofactor for proper eNOS coupling activity (4,16,17,24).…”
mentioning
confidence: 99%
“…This response of depressed H 4 B levels remained until the end of the experimental protocol for both strains of animals. Oral administration of folic acid (FA), which has been shown to reduce AAA development in these two animal models (10,29), increased both circulating and tissue levels of H 4 B starting at week 1, with H 4 B levels remaining enhanced until the end of the experiment. Linear correlation was found between tissue and plasma levels of H 4 B under both H 4 B reduced and enhanced conditions, suggesting that plasma levels of H 4 B accurately predicts its tissue levels.…”
mentioning
confidence: 99%
“…DHFR expression levels are reduced in the aortas of diabetic mice (45,46), angiotensin II-infused wild-type mice (47), BH4-deficient hph-1 mice, (48), ApoE gene knockout mice (49), and aged hypercholesterolemic LDL receptor gene knockout mice (50), which all correlates with reduced vascular BH4 levels and NO bioactivity. Where examined, restoration of DHFR levels via endothelium-targeted overexpression of the DHFR gene or folic acid supplements prevents eNOS uncoupling and inhibits the degree of hypertension or aortic aneurysm in Ang II-infused hph-1 (48) or ApoE gene knockout (49) mice and improves endothelial function in diabetic mice (46). Accordingly, the Orana heterozygote mouse represents a promising model to further define the in vivo role of DHFR in cardiovascular disease, similar to the hph-1 mouse also generated by ENU mutagenesis as a model of BH4 deficiency due to 90% constitutive reduction in GTPCH-1 activity (51).…”
Section: Discussionmentioning
confidence: 99%